A review of flexible robotic gripping systems - Tarhan, Bahadir; Asif, Seemal; Webb, Phil; Chacin, Marco (Frontiers in Manufacturing Technology, 2025)
The rapid advancement and expanding application of robotics in various sectors necessitate the development of versatile and efficient gripping systems. Robotic grippers, serving as the primary interface between robots and the physical world, are pivotal for the success of robotic applications ranging from industrial automation to delicate tasks in healthcare. This paper delves into the diverse landscape of robotic grippers, examining their design principles, material choices, and the intricate balance between flexibility and strength required to cater to a broad spectrum of operational demands. It further explores the spectrum of actuation mechanisms that empower these grippers, from traditional electric and pneumatic systems to cutting-edge soft robotics technologies that offer unprecedented adaptability and safety. The integration of sensors within grippers, enhancing their intelligence and autonomy, is also scrutinized, alongside a critical evaluation of control strategies that range from conventional PID controllers to sophisticated machine learning algorithms. In addition, this paper emphasizes the significance of real-time control and adaptation in ensuring robots’ ability to respond promptly to environmental changes, leveraging fast data processing and feedback mechanisms for improved performance. The aim of this comprehensive review is not only to provide a foundational understanding of the current state of robotic gripper technology but also to highlight key considerations and emerging trends that will shape the future of robotic manipulation. Through this exploration, the paper seeks to equip designers, engineers, and researchers with the insights needed to innovate and advance the field of robotic gripping systems.